Current landscape of dyslipidemia-related randomized clinical trials registered on the International Clinical Trials Registry Platform - Pei, Ling; Su, Muzhen; Yakeya, Reyihannisha; Hu, Zhaoqian; Abudurexiti, Aikedan; Lin, Xiaochan; Zhao, Hongmei; Abudourexiti, Gulisitan; Sidike, Abudulimu; Li, Xiaoli (Frontiers in Public Health, 2025)
IntroductionThis study elucidates the characteristics of randomized clinical trials (RCTs) related to dyslipidemia that are registered on the International Clinical Trials Registry Platform (ICTRP) to better identify research hotspots, address existing gaps, and improve clinical trial designs.MethodsThis cross-sectional study included dyslipidemia-related RCTs registered on the ICTRP up to 13 August 2024. We evaluated the relevant characteristics of these RCTs and reviewed their publication status after enrollment using PubMed.ResultsA total of 2,410 dyslipidemia-related RCTs were analyzed. The number of registered RCTs sharply increased in 2005 (N = 125). The majority of the RCTs included adults (91.4%), with a median sample size of 93 (50–229), and 92.9% of these trials had no sex-based enrollment restrictions. Few RCTs focused on participants aged ≤18 years (2.8%), those aged 19–44 years (3.4%), or exclusively women (2.8%). Medication (83.1%) was the most common type of intervention. Efficacy and safety outcomes were predominant (81.5%), while only 0.7% of the RCTs specified treatment adherence as a primary outcome. The RCTs involving adults had larger sample sizes (median 100.0 [50, 245] vs. 56.0 [27, 108], p = 0.047) and lower proportions of natural medicine and extracts (26.6% vs. 33.6%, p < 0.001) compared to age-specific RCTs. After enrollment, the 7-year cumulative publication rate was 20.8%.ConclusionsHigh-quality RCTs involving younger participants, women, and adherence-related outcomes were lacking. Researchers should prioritize exploring novel therapeutic strategies to improve trial publication rates.